Advances and trends in the application of functional near-infrared spectroscopy for pediatric assessments: a bibliometric analysis - Gao, Lin; Lin, Qianqi; Tian, Dong; Zhu, Siying; Tai, Xiantao (Frontiers in Neurology, 2024)
Objective: The objective is to elucidate the collaboration and current research status in the pediatric field of fNIRS using bibliometric analysis, and to discuss future directions. Method: Bibliometric analysis was conducted on publications related to pediatric fNIRS research published before June 2024 in the Web of Science Core Collection using VOSviewer software and R language. Results: A total of 761 documents were retrieved, published by 2686 authors from 893 institutions across 44 countries in 239 journals. The number of publications has significantly increased since 2012. The United States is the country with the highest number of publications, University College London is the institution with the most publications, Lloyd-Fox Sarah is the author with the most publications and significant influence, and "Neurophotonics" is the journal with the most publications. The current hotspots mainly involve using fNIRS to study executive functions and autism spectrum disorders in children. Conclusions: The study provides useful reference information for researchers by analyzing publication numbers, collaborative networks, publishing journals, and research hotspots. In the future, there should be an emphasis on enhancing interdisciplinary and international collaboration to collectively dedicate efforts towards the advancement of fNIRS technology and the standardization of research.